PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA SISTEM INFORMASI JASA FOTOGRAFI BERBASIS WEB DI CLOUDPHOTO - Fabian Nawami; Tuti Rohayati; Rian Dwicahya Supriatman (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
The development of the photography industry today is not only determined by the quality of the final photos but also by the convenience and ease of service received by customers. CloudPhoto Studio Ciamis still relies on manual methods to serve its customers, such as through WhatsApp and Instagram, which often lead to problems such as delayed confirmations, poorly organized data, and inconsistent services. This condition highlights the need for a more structured and interactive web-based information system to improve service quality. This research applies the concept of Customer Relationship Management (CRM) in the development of a web-based information system designed to enable customers to make reservations, access package and price information, view portfolios, and experience faster, more efficient, and personalized services. The prototype method was used in this study, emphasizing user involvement at every stage. The process begins with communication to gather requirements, quick plan to outline a simple strategy, quick design to produce the initial interface, construction of prototype to develop the system prototype, and delivery & feedback to refine the system based on user input. The results show that the implementation of this web-based CRM system can improve service efficiency, strengthen the professional image of CloudPhoto Studio, and maintain customer loyalty through more personalized services. Furthermore, the system also creates opportunities for the studio to expand its market reach more effectively. Thus, the development of a CRM-based information system can be considered a crucial strategy to support the sustainability and competitiveness of the photography industry.